Development of learning module through e-learning on semiconductor power components and systems inverters material - Monika Danni Juwita; K. Krismadinata; S. Sukardi (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Learning modules through E-Learning is designed to be able to improve the results of student learning motivation and learning. This study use Research and Development method and procedure development Plomp (preliminary research, prototyping phase, the assessment stage). The results obtained from the study of the development of the learning modules through E-Learning expressed by experts as valid media, practical response based on faculty and students, as well as effective in improving learning outcomes and motivation student learning. Based on the findings of this study it was concluded that learning modules through E-Learning can be used as learning materials on power semiconductor components and material system of inverter.